An Overview of MicroRNAs as Biomarkers of ALS - Joilin, Greig; Leigh, P. Nigel; Newbury, Sarah F.; Hafezparast, Majid (Frontiers in Neurology, 2019)
Amyotrophic lateral sclerosis (ALS; MND, motor neuron disease) is a debilitating neurodegenerative disease affecting about 4000 people each year in the UK. There is currently no cure for this disease, and its causes are relatively unknown. Diagnosis is based on a year-long battery of clinical tests, with no robust markers of diagnosis or disease progression currently identified. A major thrust of current research is to identify potential non-invasive markers ('biomarkers') in body fluids such as blood and/or cerebrospinal fluid (CSF) to use for diagnostic or prognostic purposes. Non-coding RNAs (ncRNAs), including microRNAs (miRNAs), are found at detectable and stable levels in blood and other bodily fluids. Specific ncRNAs can vary in levels between ALS patients and donors without the disease. In this review, we will provide an overview of early findings, demonstrate the potential of this new class as biomarkers, and discuss future challenges and opportunities taking this forward to help patients with ALS.